Penerapan Media Circle Life PopArt untuk Meningkatkan Kreativitas Siswa melalui Model Pembelajaran Project Based Learning di Kelas IV SDN Beji 1 Kota Batu - Galih Ayu ningtyas; Sri Indahyani; Agung Deddiliawan Ismail (Reforma : Jurnal Pendidikan dan Pembelajaran, 2023)
The development of the field of education in Indonesia expects students to have several skills such as creativity to be invaluable skills. The ability to think outside the box, generate new ideas, and create innovative solutions is essential to adapting to change and finding new ways to solve problems. One of the learning models that can be used to increase creativity is in accordance with the current curriculum using a project-based learning model and the use of circle life popart media This research uses the Classroom Action Research (PTK) method with a qualitative descriptive method. Descriptive methods are methods used to do so, explain or analyze research results, used to draw broader conclusions. This type of research examines learning activities in the form of actions that are consciously initiated and carried out together in the classroom. Based on the results of research conducted at SDN Beji 1 Batu, researchers concluded that learning using circle life popart media is fun and attracts students' attention, so that learning takes place not boring. Similarly, the application of the PjBL learning model makes students active in the learning process from the initial problem-solving activities to making projects with the media, and in learning takes place the teacher only becomes a facilitator. Previously, students could not be free to explore and create, after this learning, students better understood the topic being studied than during monotonous learning by just lecturing, telling stories, or doing questions in the LKS book. The use of circle life popart media also makes students more able to develop themselves to be creative with existing media. Similarly, the application of the PjBL learning model makes students active in the learning process from the initial problem-solving activities to making projects with the media, and in learning takes place the teacher only becomes a facilitator.